2021
DOI: 10.1108/rpj-07-2020-0180
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of irradiance on dimensional accuracy in multijet fusion additive manufacturing

Abstract: Purpose The amount of radiated energy is known to be a crucial parameter in powder-bed additive manufacturing (AM) processes. The role of irradiance in the multijet fusion (MJF) process has not been addressed by any previous research, despite the key role of this process in the AM industry. The aim of this paper is to explore the relationship between irradiance and dimensional accuracy in MJF. Design/methodology/approach An experimental activity was carried out to map the relationship between irradiance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…[ 9,26 ] However, whether SLS or MJF gives higher part density is still controversial in the literature since it may also depend on the process parameters adopted to produce the parts (i.e., laser power, scan speed, and scan spacing for SLS and print profile and lamps irradiance for MJF), that are strictly confidential for MJF. [ 25,32,33 ] For example, Xu et al [ 10 ] found a lower amount of porosity in neat PA12 samples produced by SLS, while Abbott et al [ 16 ] got the opposite results; other authors [ 25,26 ] reported similar values for both techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9,26 ] However, whether SLS or MJF gives higher part density is still controversial in the literature since it may also depend on the process parameters adopted to produce the parts (i.e., laser power, scan speed, and scan spacing for SLS and print profile and lamps irradiance for MJF), that are strictly confidential for MJF. [ 25,32,33 ] For example, Xu et al [ 10 ] found a lower amount of porosity in neat PA12 samples produced by SLS, while Abbott et al [ 16 ] got the opposite results; other authors [ 25,26 ] reported similar values for both techniques.…”
Section: Resultsmentioning
confidence: 99%
“…[29,30,32] However, details about the process parameters (e.g., lamps irradiance and speed) are not revealed by HP for intellectual property reasons. [25,33] The layer height was set at 80 μm, as recommended by the printer manufacturer.…”
Section: Experimental Section 21 Materials and Printing Equipmentmentioning
confidence: 99%